The Ratio of CTLA4 to Perforin and Granzyme B as a Potential Biomarker of Tolerance in Chimeric Renal Transplant Patients. (July 2018) - Khalil, Ahmed; Chhabra, Anita; Merchak, Andrea; Kahn, Larry; Leventhal, Joseph; Ildstad, Suzanne
Abstract : Background: Thirty-six subjects have been enrolled in a phase II clinical trial aimed to induce tolerance through chimerism. Each subject received FCRx (mPBMC enriched in donor hematopoietic stem cells and facilitating cells) preceded by nonmyeloablative conditioning with kidney transplant (KTx) one day before infusion. Twenty-six stable donor chimeric subjects (SDC) have been weaned safely off immunosuppressive drugs (IS) (time off IS 1-88 mos) with no evidence of rejection on protocol biopsy. Transiently donor chimeric subjects (TDC) were not weaned off IS and were maintained on low dose tacrolimus monotherapy. Rationale: Suthanthiran et al. (ATC 2017) reported on urinary cell mRNA profiling of the FCRx group at 3 years post KTx and found a lower expression of granzyme B and perforin mRNA in SDC subjects compared to TDC subjects. The ratio of CTLA4 to perforin + granzyme B was significantly higher in SDC subjects compared to TDC subjects. The aim of the present study is to determine if a similar ratio in PBMCs could be predictive of tolerance. Additionally, identifying the immune cells that contribute to the production of CTLA4, perforin and granzyme B may provide information on the mechanism of tolerance. Methods: Cryopreserved PBMC obtained at 9-12 months after KTx plus FCRx from five SDC subjects and one TDC subject were analyzed by flow cytometry for CTLA4, perforin and granzyme B expression. Results: The expression of both cytotoxic granzyme B and perforin by total lymphocytes was lower in SDC subjects compared to TDC subject (Figure 1). The ratio of CTLA4 to perforin + granzyme B was higher in SDC subjects compared to TDC subject (Figure 2). Our preliminary data mirrors the urinary profile, suggesting that it may be useful as a potential biomarker of tolerance (Figure 1) SDC subjects (blue) have lower expression of perforin and granzyme B compared to TDC (orange) subjects (Figure 2) The ratio of CTLA4/granzyme B + perforin is higher in SDC (blue) compared to TDC (orange) (Table 1) Preliminary data Figure. No caption available. Figure. No caption available. Conclusion: The ratio CTLA4 to perforin + granzyme B may be useful as a potential biomarker of tolerance.